2020
DOI: 10.1111/1365-2745.13507
|View full text |Cite
|
Sign up to set email alerts
|

Beyond seedlings: Ectomycorrhizal fungal networks and growth of mature Pseudotsuga menziesii

Abstract: Mycorrhizal networks are conduits for the transfer of resources between hosts. While ectomycorrhizal networks (EMN) are known to influence seedlings, their effect on adult tree growth remains unknown and may have important implications for forest responses to future climates. We used annual basal area increment of trees and previously described Rhizopogon vesiculosus and Rhizopogon vinicolor EMNs to examine an association between the number of connections between trees through an EMN and the growth of adult in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…We sanded increment cores with progressively finer sandpaper to 6‐micron grit. We visually cross‐dated each core prior to measuring using CDendro (Cybis Elektronik & Data AB) for the cores from British Columbia (0.01 mm resolution; Birch, Simard, et al, 2021) and a Velmex measuring system (Velmex Inc) for the Utah cores (0.001 mm resolution). We verified cross‐dating with the COFECHA program (Holmes, 1983) and dplR 1.7.0 (Bunn et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We sanded increment cores with progressively finer sandpaper to 6‐micron grit. We visually cross‐dated each core prior to measuring using CDendro (Cybis Elektronik & Data AB) for the cores from British Columbia (0.01 mm resolution; Birch, Simard, et al, 2021) and a Velmex measuring system (Velmex Inc) for the Utah cores (0.001 mm resolution). We verified cross‐dating with the COFECHA program (Holmes, 1983) and dplR 1.7.0 (Bunn et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, fungal communities may shift with edaphic variation, rooting density and stand development (LeDuc et al, 2013; Odriozola et al, 2020; Twieg et al, 2007), which could alter the outcome of competition between mycorrhizal fungi and reduce the influence of priority effects (Kennedy et al, 2007). Older trees could exhibit greater selection pressures compared to younger trees owing to the time over which selection pressures influence fungal communities or through tree ontogenesis and senescence altering nutrient requirements (Bertrand et al, 2011; Birch, Simard, et al, 2021; Peri et al, 2006; Tang et al, 2014). The time over which selection pressures occur could also influence fungal communities by causing more pronounced changes over time.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that the majority of EM species sampled from Cedar Breaks fungal communities (54.4%) occurred on more than one tree species and were capable of forming interspecific mycorrhizal networks (Birch et al 2021a). Likewise, mycorrhizal connectivity among distantly related heterospecific trees is well-described in Douglas-fir forests like Wind River (Simard et al 1997, Birch et al 2021b. The evidence shown here constitutes a first approximation of multitrophic plant-enemy-mutualist dynamics in western forests, a basis for which future studies may conduct direct sampling of mycorrhizae and plant defensive chemistry to illuminate the complex relationship between plant diversity, fungal diversity, and plant mortality susceptibility.…”
Section: Discussionmentioning
confidence: 54%
“…1997, Birch et al. 2021 b ). The evidence shown here constitutes a first approximation of multitrophic plant–enemy–mutualist dynamics in western forests, a basis for which future studies may conduct direct sampling of mycorrhizae and plant defensive chemistry to illuminate the complex relationship between plant diversity, fungal diversity, and plant mortality susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Since the early 2000s and the first evidence of the pivotal role of ECM CMNs in the dynamics of temperate plant communities during both primary ( Nara, 2006a ) and secondary successions ( Simard et al, 1997 ), the ecological significance of ECM fungal-mediated interactions among plants has been a matter of ongoing debate ( Bever et al, 2010 ; Birch et al, 2020 ). As a consequence, our understanding of the physical nature, functional boundaries, and trophic influence of ECM CMNs has considerably increased for the last decade, propelled by both the emergence of powerful metabarcoding tools and the deployment of a variety of experimental approaches in order to decipher underground ECM-based processes.…”
Section: Introductionmentioning
confidence: 99%